Smoking, Physical Activity, and Hypertension Incidence Among Older Adults in Malang, Indonesia - Faiqoh, Maimanah Zumaro Ummi; Laksnadi, Ardiar Rahmananda; Hartawan, Safira Shafa Rachmah; Abidanovanty, Felisita Maritza; Qoth'i, Ikhsanuddin; Susetiyo, Karindra Amadea; Angeli, Anastasia Pearl; Handayani, Samsriyaningsih; Widodo, Heri Sugeng (Universitas Airlangga, 2023)
Hypertension is a crucial health concern that requires attention, and it can be influenced by factors such as smoking and physical activity. According to a study conducted at Lawang Health Center, Malang, Indonesia, in 2020, 13.5% of the population in RW 05, Bedali Village, Malang, suffered from hypertension. It was one of the top three prevalent diseases in the village, especially among individuals aged over 69 years. The objective of this research was to examine the relationship between smoking, physical activity, and the occurrence of hypertension among older adults in RW 05, Bedali Village, Lawang, Malang. The study employed a case-control analytic observational method, involving 25 cases and 25 controls within the older adult age group (>45 years). The participants consisted of 50 individuals, including 23 men and 27 women. Among the respondents, 23 were smokers, while 27 were non-smokers. Additionally, 25 respondents engaged in light physical activity, whereas 25 respondents had moderate to vigorous physical activity levels. The analysis indicated a significant correlation between smoking, physical activity, and the prevalence of hypertension among older adults in RW 05, Bedali Village, Lawang, Malang, with a p-value of 0.005 for each factor.